Enhancing Afforestation Success: Seedling Survival and Growth in Relation to Planting Pit Digging and Vegetation Control in Rashaya Al-Wadi, Lebanon - Saleh, Mohammad; Baydoun, Safaa; Mostafa, Wael; Salman, Hisham; Borjac, Jamilah (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Afforestation is vital for environmental conservation but is hindered in arid and semi-arid regions by water scarcity and competitive vegetation. This study evaluates three pit-digging methods (traditional pits, hoedad, and auger tools) and three vegetation control strategies (mulching, mowing, and herbicide) in Rashaya al-Wadi, Lebanon. Six tree species (Quercus calliprinos, Quercus infectoria, Pistacia palaestina, Pinus pinea, Pinus halepensis, and Cedrus libani) were assessed using a randomized complete block design with 12 treatment combinations replicated across four blocks. Seedlings were planted with uniform spacing, and vegetation controls were applied once at planting. Survival and growth, measured biannually over two years as height and root collar diameter (RCD), were analyzed using ANOVA. Survival was highest with mulch (51%), followed by herbicide (35%), and lowest with mowing (1.2%) and control (1.4%). Height growth ranged from 6.75–30.44 cm with mulch, 3.72–36.89 cm with herbicide, 1.92–5.25 cm with mowing, and 1.81–6.08 cm with control. RCD growth followed similar trends. Traditional pits achieved the highest survival, while the hoedad tool had the lowest. Findings demonstrate that mulching with traditional pits enhances afforestation success and offers a sustainable solution for semi-arid regions. Further research is needed to refine methods for diverse sites. Keywords: afforestation success, competitive vegetation, environmental conservation, pit-digging methods, seedling survival